2008
DOI: 10.2337/db07-1331
|View full text |Cite
|
Sign up to set email alerts
|

HLA DR-DQ Haplotypes and Genotypes and Type 1 Diabetes Risk

Abstract: OBJECTIVE-The Type 1 Diabetes Genetics Consortium has collected type 1 diabetic families worldwide for genetic analysis. The major genetic determinants of type 1 diabetes are alleles at the HLA-DRB1 and DQB1 loci, with both susceptible and protective DR-DQ haplotypes present in all human populations. The aim of this study is to estimate the risk conferred by specific DR-DQ haplotypes and genotypes.RESEARCH DESIGN AND METHODS:-Six hundred and seven Caucasian families and 38 Asian families were typed at high res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
585
8
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 686 publications
(637 citation statements)
references
References 44 publications
30
585
8
14
Order By: Relevance
“…This feature is also absent from the HLA-DQ4 peptide-binding motif. 29 An immortalized homozygous HLA-DR8 cell line carrying the T1D-associated HLA-DR8-DQ4 haplotype 6 was used for the analysis. There is little information about peptides binding DR8 and no concrete information about the peptide-binding motif.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This feature is also absent from the HLA-DQ4 peptide-binding motif. 29 An immortalized homozygous HLA-DR8 cell line carrying the T1D-associated HLA-DR8-DQ4 haplotype 6 was used for the analysis. There is little information about peptides binding DR8 and no concrete information about the peptide-binding motif.…”
Section: Discussionmentioning
confidence: 99%
“…A dose effect of this polymorphism in relation to the risk of T1D has not been established, although the highest association corresponds to a haplotype without Asp57 in both DR and DQ b-chains (DRB1*0405/DQA1*0301-DQB1*0302) (ref. 6) and the highest protection to the DR15 haplotypes, with Asp57 in both DR and DQ b chains (DRB1*15/DQA1*0102-DQB1*06). However, the presence of only one DQ allele lacking Asp57 appears to be enough for susceptibility, as it is the case for DR3 and the other associated DR4 haplotypes (Supplementary Table 2).…”
Section: Hla-dr8-binding Motif L Muixí Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…The most important susceptibility factors reside within the major histocompatibility complex (MHC) where particular human leukocyte antigen (HLA) class II DRB1-DQA1-DQB1 haplotypes confer high disease risk. 1,2 However, numerous studies have strongly implicated additional T1D risk loci within the MHC. [3][4][5][6][7][8][9][10][11][12] This complex contains an unusually high density of genes involved in immunological responses, 13 of which many are good candidates for involvement in autoimmune processes.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies have shown that particular combinations of class II HLA alleles of the DRB1, DQA1 and DQB1 loci determine the extent of risk of developing T1D. High genetic risk conferring susceptibility to T1D have been reported for the DR3-DQ2 (DRB1*0301-DQA1*0501-DQB1*0201) and DR4-DQ8 haplotypes (DRB1*0401-DQA1*0301-DQB1*0302), in particular for heterozygous subjects (Erlich et al 2008). Since the physiological role of these class II molecules is to present peptide epitopes to CD4 + T lymphocytes, most studies focused on the role of CD4 + T lymphocytes in T1D pathogenesis.…”
Section: Genetics: Focus On Hlamentioning
confidence: 99%